APPLICATION TYPE OF MULCH ON PLANTING FIVE TRYPES OF POTENTIAL ENERGY PLANTS IN PRIVATE FOREST OF VILLAGES AROUND GUNUNG GEULIS, SUMEDANG, WEST JAVA - DAMAYANTI (NIM : 11514026), SILVI
Several types of potential energy crops can be developed in the private forest around mount Geulis, but so far the community has not realized the potential of several energy crops so that they have not been widely utilized. In addition, the productivity of private forests still tends to be low, one of the causes is less maintenance techniques at the beginning of growth. Weed is one of the factors driving the decline in wood productivity in private forests. Eradicating weeds so far requires expensive time and cost so we need effective weed eradication techniques, namely mulch. Wood productivity can be seen from the stem diameter, stem height, number of leaves, biomass and environmental conditions and the presence of weeds. Therefore this study aims to determine the type of mulch to plant growth, environmental conditions (temperature and soil moisture) and the presence of weeds. This research was carried out on the private forest land of Jatiroke village by planting potential energy plant seeds. Planting method was carried out using Factorial Randomized Block Design with factors giving 4 types of mulch (infarboard, oil paper, banana midrib and without mulch) on 5 species (G. arborea, P. falcataria, C. arabica, A. cadamba and A. mangium ) which is repeated 3 times so there are 60 test units. The results of this study can be seen that the potential energy plant species have the largest increase in diameter is G. arborea by giving oil paper mulch (0.53 cm), while the highest increase in stem height was found in P. falcataria by banana midrib mulch (17.6 cm) and the highest number of leaves was found in G. arborea by applying oil paper mulch (34 strands) and the largest seed biomass was found in A. cadamba by infraboard mulch (32.04 grams). Various types of mulch have an influence on environmental conditions where the lowest soil temperature is found in banana midrib mulch (23.28oC) and the highest soil temperature is found in plants with infraboard mulch (25.03oC). The highest soil moisture was found in plants with mulch infraboard (85.43%) and the lowest was in plants without mulch (72.55%). The most weed density was found in plants without mulch (32.85%) and the least weed density was found in plants with infraboard mulch (23%).